185k views
0 votes
Please helppppppppppppppppppppppppppp ;—;

Please helppppppppppppppppppppppppppp ;—;-example-1

2 Answers

2 votes

a) (i) and (ii)

b) (i) and (iii)

c) (ii) and (iii)

d) (ii) and (iii)

e) I don't think any of them are equivalent... please correct me if I am wrong.

f) (i) and (ii)

User Shadowed
by
6.3k points
4 votes

Answer:

(a) i and ii: 2b-2 = b+b-2

(b) i and iii: c+d = d+c

(c) ii and iii: a + 2b - 1 = a+b-1+b

(d) i and iii: x+(y-z) = x-(z-y)

(e) ii and iii: (a-1)² = (1-a)²

(f) i and ii: 3a-b-1-1 = 3a+b-2-2b

Explanation:

let me know if you require detailed explanation for any of them.

User Jon Snow
by
6.4k points